(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The vanadium dioxide is a material thermo chromium which sees its optical properties changing at the time of the transition from the phase of semiconductor state†” metal, at a critical temperature of 68°C. The study of the optical properties of a thin layer of VOâ‚‚ thickness 82 nm, such as the dielectric function, the index of refraction, the coefficient of extinction, the absorptions coefficient, the reflectivity, the transmittivity, in the photonic spectrum of energy Ï‰ located in the interval: 0.001242 â‰¤ Ï‰ (ev) â‰¤ 6, enables us to control well its practical utility in various applications, like the intelligent panes, the photovoltaic, paintings for increasing energy efficiency in buildings, detectors of infra-red (I.R) or ultra-violet (U.V). We will make simulations with Maple and compare our results with those of the literature